The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.5130/ccs.v2i2.1512
|View full text |Cite
|
Sign up to set email alerts
|

Lords of the Square Ring: Future Capital and Career Transition Issues for Elite Indigenous Australian Boxers

Abstract: In Australia a serious and widely documented statistical gap exists between the socio-economic circumstances of the country's Indigenous and non-Indigenous populations. Areas of divergence include life expectancy, health, housing, income, and educational opportunity and employment. This has made entry into an occupation or vocation problematic for some Aboriginal people. While sport has provided opportunities for a small number of talented Indigenous athletes, it has rarely been a pathway to lifelong prosperit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Collegiate student-athletes can become over-identified with athletics, which causes them to neglect career options and academics (Anderson, 2012;McGillivray, Fearn, & McIntosch, 2005). Histor-ically, collegiate student-athletes are far behind their non-student-athlete peers when it comes to planning for a career due to their lack of goal setting, career salience, and career decision-making abilities hindered by their sport involvement (Taylor & Pompas, 1990;Martinus, 2007;Stronach & Adair, 2010). Anderson (2012) and Lavallee and Robinson (2007) warned that career uncertainty could lead to vulnerability, anxiety, and in some cases unemployment when athletic careers ended.…”
Section: Transition and Loss Of Athletic Identitymentioning
confidence: 99%
“…Collegiate student-athletes can become over-identified with athletics, which causes them to neglect career options and academics (Anderson, 2012;McGillivray, Fearn, & McIntosch, 2005). Histor-ically, collegiate student-athletes are far behind their non-student-athlete peers when it comes to planning for a career due to their lack of goal setting, career salience, and career decision-making abilities hindered by their sport involvement (Taylor & Pompas, 1990;Martinus, 2007;Stronach & Adair, 2010). Anderson (2012) and Lavallee and Robinson (2007) warned that career uncertainty could lead to vulnerability, anxiety, and in some cases unemployment when athletic careers ended.…”
Section: Transition and Loss Of Athletic Identitymentioning
confidence: 99%
“…Educational involvement and career 261 planning were also positively associated with post-sport life adjustment among college 262 athletes (Lantz, 1995), and athletes attributed their limitation of life choices after sport career 263 termination to a lack of personal development (Chow, 2001; Stronach & Adair, 2010;Swain, 264 1991). 265…”
mentioning
confidence: 99%
“…Furthermore, a successful professional sports person will already have experienced other transitions from amateur, youth and pre-professional to a more elite level which requires greater and increasing dedication to sports activities, resulting in, one could argue, less time to spend on other life activities (Baker et al, 2003). A drive to excel at sport may engender a lack of skill in dealing with non-sport activities (simply due to intensive focus elsewhere) and a less developed understanding around life choices (Stronach and Adair, 2010). Research has illustrated that former athletes showed difficulties dealing with non-sport situations.…”
Section: A Review Of Sports-career Oriented Scholars' Interestsmentioning
confidence: 99%
“…Studies have found that athletes have attributed limited life choices post professionally playing sport to a lack of opportunities for personal development (e.g. Chow, 2001;Stronach andAdair, 2010 andSwain 1991). Professional sports people, it is argued; regard post-play planning when actively competing as a distraction from their sport performance (Petitpas et al, 1992).…”
Section: Social Career and Bodily Capital -Explanatory Potential Formentioning
confidence: 99%